INVESTMENT ON ESG-PRINCIPLES AS A DETERMINING FACTOR OF INFLUENCE ON THE COMPETITIVENESS OF METALLURGICAL ENTERPRISES - TKACHENKO, ALLA; KOLESNIK, ELEONORA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article states that the traditional model of economic growth of metallurgy due to the export of energy-intensive products no longer works, new impulses and effective tools are needed to transform the current model of economic growth to the latest model – the model of low-carbon production. Emphasis is placed on the importance of ESG-investment in the process of transformation to a low-carbon economy and its impact on the competitiveness of enterprises. It is substantiated that the introduction of ESG-investment requires the formation of a certain regulatory environment, and accordingly to clarify the substantive component of this concept and its operationalization, bringing the concept to a form that will work with it on a practical level, operate it in solving specific analytical and forecasting tasks, verify or refute research hypotheses. The author’s definition of ESG investing is proposed as an investment aimed at minimizing ESG risks, reducing environmental pollution to levels that do not harm human health and natural ecosystems, as well as strengthening social responsibility and improving corporate governance. It is substantiated that Ukraine’s delay in ratifying international regulations on the introduction of ESG-investing and ignoring the world experience in creating a regulatory environment for investing in ESG-principles threatens metallurgical enterprises with the loss of investors and, accordingly, competitive positions in the global metal market. Using specific examples from world experience, the need to recognize the standardization of reporting on the impact of business on climate and environment, one of the priority issues in the formation of the regulatory environment of ESG-investment. An arsenal of effective measures for the formation of the regulatory environment of ESG-investment, the introduction of which in domestic practice will allow to make effective and optimal management decisions to maintain the position of domestic metallurgical enterprises in the TOP-10 leading countries in metal production.